HISTOLOGICAL EVALUATION OF RENAL DAMAGE IN DIABETIC WISTAR RATS TREATED WITH ETHANOL LEAF EXTRACT OF Pterocarpus Mildbraedii (WHITE PADOUK) - Nweke, Elizabeth Obioma; Nweke, T. M.; Ezejiegu, C. O.; Azunna, U.; Ogwo, E. U.; Ubani, C. D. (FUDMA Journal of Sciences, 2026)
Chronic hyperglycemia significantly contributes to diabetes-related kidney damage. Since the kidneys play a crucial role in drug metabolism and excretion, renal recovery in diabetic individuals may be impaired. This study evaluated the renal health of diabetic Wistar rats after oral administration of the ethanolic leaf extract of Pterocarpus mildbraedii (ELEPM).Thirty adult Wistar rats were divided into six groups (n = 5). Diabetes was induced in Groups II–VI using 120 mg/kg alloxan intraperitoneally. Group I served as the non-diabetic control; Group II was diabetic but untreated. Groups III, IV, and V received 100 mg/kg, 200 mg/kg, and 400 mg/kg of ELEPM, respectively, while Group VI received 2.5 mg/kg of metformin. Treatments lasted 21 days. Body weights were recorded at the beginning and end, after which animals were sacrificed and blood samples collected. Histological and biochemical analyses were conducted using standard methods. All groups except the untreated diabetic group showed weight gain. ELEPM at 400 mg/kg demonstrated the most pronounced antihyperglycemic effect among the extract doses, though still significantly (p<0.05) less effective than metformin. Serum urea and creatinine levels were significantly higher (p<0.05) in the untreated diabetic group compared to the ELEPM-treated groups. Histological assessment of rats given 400 mg/kg ELEPM revealed moderate renal regeneration with mild fatty changes and tubular distortion. Oral administration of ELEPM, particularly at 400 mg/kg, shows promise in mitigating hyperglycemia and renal damage in diabetic conditions, suggesting potential as a supportive therapy for diabetic nephropathy.